2018
DOI: 10.1029/2018gh000145
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Particulate Matter Size Distributions Drive Regional and Global Variability in Particle Deposition in the Respiratory Tract

Abstract: Human exposure to airborne particulate matter (PM) increases the risk of negative health outcomes; however, substantial uncertainty remains in quantifying these exposure‐response relationships. In particular, relating increased risk of mortality to exposure to PM with diameters smaller than 2.5 μm (PM2.5) neglects variability in the underlying size distribution of PM2.5 exposure and size‐resolved deposition in human airways. In this study, we combine a size‐resolved respiratory particle‐deposition model with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 92 publications
(129 reference statements)
2
35
0
Order By: Relevance
“…EA, for all respiratory tract regions. This is consistent with the findings of Kodros et al (2018), which reported high aerosol mass deposited concentrations in the human respiratory tract for India and Eastern China. Cities in NAAN and EU are associated with E / !$ lower in magnitude compared to the other geographical regions.…”
Section: Geographical Variations In Size-resolved Urban Aerosol Mass supporting
confidence: 93%
See 4 more Smart Citations
“…EA, for all respiratory tract regions. This is consistent with the findings of Kodros et al (2018), which reported high aerosol mass deposited concentrations in the human respiratory tract for India and Eastern China. Cities in NAAN and EU are associated with E / !$ lower in magnitude compared to the other geographical regions.…”
Section: Geographical Variations In Size-resolved Urban Aerosol Mass supporting
confidence: 93%
“…However, the full extent of the mass RTDDRs for LA and WA in the coarse mode cannot be reliably characterized due to the lack of mass PSD observations in the two regions. As shown in Kodros et al (2018), desert regions of WA and AF are associated with very high deposited mass concentrations in the human respiratory tract.…”
Section: Geographical Variations In Size-resolved Urban Aerosol Mass mentioning
confidence: 93%
See 3 more Smart Citations